2019
DOI: 10.1002/pssr.201900519
|View full text |Cite
|
Sign up to set email alerts
|

Proton Irradiation on Cesium‐Fluoride‐Free and Cesium‐Fluoride‐Treated Cu(In,Ga)Se2 Solar Cells and Annealing Effects under Illumination

Abstract: Several studies have been performed on proton irradiation onto alkali‐metal untreated Cu(In,Ga)Se2 (CIGS) solar cells. However, there are almost no studies describing similar effects on alkali‐treated CIGS solar cells. With this motivation, this work investigates proton irradiation and annealing effects under illumination on cesium‐fluoride‐free (CsF‐free) and CsF‐treated CIGS solar cells. Both CsF‐free and CsF‐treated CIGS solar cells degrade under proton irradiation. External quantum efficiency measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…27) This finding suggests that the NiO/ZnO solar cells are expected to be operational for extended periods in space. In addition, the proton fluence for initiating the degradation of the NiO/ZnO solar cells was higher than that for the CIGS 21,22) and GaAsbased solar cells. 28) This implies that among the solar cells for space-related applications, the NiO/ZnO solar cells showed the potential of higher tolerance for proton radiation, as observed in the present study, as well as for electron radiation, as identified in previous studies.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…27) This finding suggests that the NiO/ZnO solar cells are expected to be operational for extended periods in space. In addition, the proton fluence for initiating the degradation of the NiO/ZnO solar cells was higher than that for the CIGS 21,22) and GaAsbased solar cells. 28) This implies that among the solar cells for space-related applications, the NiO/ZnO solar cells showed the potential of higher tolerance for proton radiation, as observed in the present study, as well as for electron radiation, as identified in previous studies.…”
mentioning
confidence: 92%
“…The proton fluence ranged from 1 × 10 12 cm −2 to 1 × 10 16 cm −2 . Because we used a 380 keV proton beam to investigate the physical properties of CIGS solar cells, 21,22) the same conditions were selected for comparison purposes. The solar cell performance before/after proton irradiation was evaluated via the J-V measurements under AM 1.5 conditions.…”
mentioning
confidence: 99%
“…Therefore, the obvious degradation of V OC may be caused by the elements diffusion at p-n heterojuction interface and/or CZTSSe bulk region. [34] The J SC reduction could also arose from the performance changes of ITO transparent conductive layer, as described by XRD results. The remaining factor of V OC , J SC , FF, and PCE as a function of the displacement damage fluences in Figure 4e also shows that V OC is responsible for a greater contribution of the reduction in efficiency.…”
Section: Resultsmentioning
confidence: 94%
“…Among different alkali metal‐treated solar cells, cesium fluoride‐treated CIGS solar cells possess the highest conversion efficiency . The radiation tolerance properties of CsF‐treated CIGS solar cells have been investigated, and high radiation tolerance was shown, similar to alkali‐untreated CIGS solar cells . This indicates that CsF‐treated CIGS solar cells are applicable to terrestrial and space applications.…”
mentioning
confidence: 97%
“…[12] The radiation tolerance properties of CsF-treated CIGS solar cells have been investigated, and high radiation tolerance was shown, similar to alkali-untreated CIGS solar cells. [24,25] This indicates that CsF-treated CIGS solar cells are applicable to terrestrial and space applications. Furthermore, our previous studies revealed the beneficial effect of heat-light soaking (HLS) [26][27][28] or heat-bias soaking (HBS) [13,28] on alkali metal-treated CIGS solar cells.…”
mentioning
confidence: 97%